Dire la conquête et la souveraineté des Hauteville en arabe (jusqu’au milieu du XIIIe siècle) - Annliese Nef (Tabularia)
In contrast to the opinion often expressed by historians that pre-1250 Arabic texts reflect their authors’ systematic lack of interest in the Latins, or even for non-Muslims altogether, some political entities did attract their authors’ attention as is the case of the 11th-12th century Sicily. The conquests and polity of the Hautevilles of Sicily have been the subject of numerous original Arabic texts in the 12th century and later. Their literary genres are diverse, yet all of them develop the same themes: prowess and military efficiency, establishment of a peaceful realm under a just ruler and the imperial pretentions of the dynasty.